Political Party Management Strategy: An Approach to Political Communication Strategy - Ardiyanti Ardiyanti; Muh. Akbar; Nur Alim Djalil (Journal La Bisecoman, 2024)
In the 2019 Legislative Election there were 19 parties participating in the election contest, of which 4 new parties passed, while in the 2024 Legislative Election there were 24 parties that passed, including 4 new parties, one of which was the Gelora Party and in South Sulawesi only 18 parties passed the election. This research aims to (1) describe the Gelora Party's communication planning in obtaining legislative seats. (2) describes the implementation of Gelora Party communications to obtain legislative seats. This research was carried out at the Gelora Party DPW Office, South Sulawesi. Data collection was carried out through observation, in-depth interviews and documentation. Data analysis uses qualitative methods with a narrative or descriptive qualitative study approach. The results of the research show that the Gelora Party's Political Communication Strategy as a New Party in the 2023 General Election continues to implement a political communication strategy in winning legislative seats, where means of supporting political communication such as creative and up-to-date social media content to support the popularity of legislative candidates, a persuasive approach is still dominant. The Gelora Party and its image as a Nationalist Party became an obstacle in gaining support from other religious groups.